Treatment of oral fungal infections using antimicrobial photodynamic therapy: A systematic review and meta-analysis - Roomaney, Imaan A (Department of Public Health and Family Medicine, 2023)
Part A is a research protocol which describes the background and proposed methodology of this systematic review. This section contains the definitions used for “photodynamic therapy”, “conventional antifungal medication” and “oral fungal infections”. It also provides details of quantitative and qualitative methods used to analyse the effectiveness of photodynamic therapy (PDT) and conventional antifungal medications in the treatment of oral fungal infections. Part B is a literature review which expands on the protocol. It provides an in-depth description of the epidemiology and pathogenesis of oral fungal infections. It also discusses currently available and future treatment strategies and the potential and shortcomings thereof. The importance of this research is highlighted by contextualising PDT as an alternative treatment modality to conventional antifungal medications. Part C presents the research as a journal manuscript according to the Photodiagnosis and Photodynamic Therapy Journal's instructions for authors. The manuscript includes a brief introduction to the research followed by a summary of the methods and presentation of the results which are then discussed.